The potential of the “Green microbiology” approach for facilitating the human capital in Kazakhstan’s chemical and petrochemical industry - Do Lana; Askarova Zifa; Srailova Gulziya; Ussenova Anel (BIO Web of Conferences, 2024)
Today, human capital is one of the main factors for the effective functioning of the modern economy. Human capital is the basis for developing any production branch, the basis on which all production is built. Therefore, analyzing human capital formation in the chemical and petrochemical industries is relevant today. The chemical and petrochemical industries are industries with high labor productivity. Analyzing human capital formation in these industries is necessary for further productivity growth and production efficiency. Therefore, the relevance of human capital formation in Kazakhstan’s petrochemical and chemical industries is increasing. The study aims to identify the problems in human capital formation in the chemical and petrochemical industries and provide the most effective approaches to solving these problems. The most innovative approach to forming human capital in the chemical and petrochemical industries is the “Green Microbiology” approach, which reduces the risks of diseases of workers in this industry.